Dormitory Fires in Kenyan Boarding Schools (2000–2026): A Scoping Review of Arson, Student Grievance, Institutional Preparedness, and Prevention - Jeketule Soko (PT. Global Research Collaboration, 2026)
Dormitory fires in Kenyan boarding schools remain a recurring school-safety crisis with serious educational, psychosocial, legal, and policy consequences. While public debate often frames these incidents as indiscipline, accidents, or infrastructural failure, Kenya-specific scholarship suggests a more complex interpretation: school arson may also function as student protest within boarding institutions marked by unequal power relations and weak channels for trusted student voice. This scoping review maps evidence on dormitory fires in Kenyan primary, junior, and secondary boarding schools from January 2000 to June 2026. Guided by PRISMA-ScR and the Joanna Briggs Institute approach, it applies a Population-Concept-Context framework and draws on 43 cited sources, including peer-reviewed literature, books, methodological guidance, government and standards documents, and NGO/IGO or rights-based reports. A supplementary incident table based on non-peer-reviewed reports identifies eight documented dormitory-fire incidents from 2001 to 2026, involving at least 125 learner deaths and at least 155 reported injuries, though some injury counts remain incomplete or contested. The synthesis identifies six themes: incident patterns; arson, grievance, and protest politics; institutional fire-safety preparedness; policy and enforcement gaps; impacts on learners and school communities; and prevention strategies. Overall, the evidence suggests deliberate fire-setting cannot be explained by individual pathology alone, but emerges from intersecting grievances, punitive school cultures, examination pressure, poor welfare, overcrowding, inadequate voice mechanisms, and weak enforcement. Prevention requires safer dormitory design, functioning alarms and exits, drills, welfare improvement, grievance systems, psychosocial support, transparent reporting, enforceable inspections, and coordinated national policy action.